Workshop on Ethnic Relations and TITAS measurement - Ahmad, Ibrahim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
17 - 18 July 2012. “Regardless of question formats, they should reflect the UMP’s vision, mission and core values.